Determinantes do conhecimento do consumidor sobre preços de bens duráveis: um exame em oito categorias de produtos - Silva, Marco Antônio (2005)
This thesis deals, based on Estelami and De Maeyer (2004) studies, with subject that merits further academic investigation: the Consumer Price Knowledge for durable goods (ESTELAMI and LEHMANN, 2001). At first, the examination in eight products categories established significant variations in the consumer price knowledge. This analysis also showed that only one third of the consumers provided products price estimates accurately, confirming the expectations that this knowledge is limited (DICKSON and SAWEYR, 1990; ESTELAMI, 1998; KRISHNA, CURRIN and SHOEMAKER, 1991). Finally, the existence of a relation between Price Knowledge and its potential determinants – Involvement with the Product, Advertising Exposure and Use of Price-Quality Relation were verified. The results pointed that, although the relation between consumer price knowledge and its potential determinants is present for some products, it is tenuous.